Study protocol: the ear-nose-throat (ENT) prospective international cohort of patients with primary ciliary dyskinesia (EPIC-PCD) - KARADAĞ, BÜLENT TANER; ERDEM ERALP, ELA (BMJ PUBLISHING GROUP, 2021)
Introduction Primary ciliary dyskinesia (PCD) is a rare, genetic, multiorgan disease with an estimated prevalence of 1 in 10 000. It affects mainly the upper and lower airways due to impaired mucociliary clearance. Almost all patients have sinonasal or otologic (ear-nose-throat, ENT) problems, although the ENT clinical phenotype may present great variability. Despite that, data on PCD ENT manifestations are scarce and based on small single-centre studies. To date, we know little about the spectrum and severity of PCD ENT disease, its association with lung disease, its course over life and its determinants of prognosis. This study protocol describes the aims and methods of the first prospective, observational, multinational cohort study focusing on ENT disease in patients with PCD. Methods and analysis The ENT prospective international cohort of patients with PCD (EPIC-PCD) is a prospective standardised observational clinical cohort set up as a multinational multicentre study, embedded into routine patient care. It aims to longitudinally characterise ENT disease in patients with PCD and its association with lung disease, and to identify determinants of its prognosis. Patients of all ages, diagnosed with PCD who undergo an ENT clinical assessment at least once a year at one of the participating centres will be invited to participate. Collected data include diagnostic test results, results of ENT examinations, lung function measurements, information on management of ENT disease and patient-reported data on clinical symptoms and health-related quality of life (QoL). Data are collected using the standardised PCD-specific FOLLOW-PCD form and the validated QoL-PCD questionnaire. Ethics and dissemination The study has been reviewed and approved by the Human Research Ethics Committees at all participating centres, based on local legislation. The results of the study will be published in scientific journals, presented at scientific conferences and disseminated to participants and national patient organisations.
Keywords: chronic airways disease; epidemiology; respiratory medicine (see thoracic medicine); audiology; paediatric otolaryngology; paediatric thoracic medicine; OTOLOGIC FEATURES; OTITIS-MEDIA; CHILDREN; MANIFESTATIONS; DEFECTS